Peningkatan Nilai Tambah Olahan Bawang Merah dengan Konsep Pengembangan Ekonomi Lokal di Kecamatan Toroh Grobogan - Dwi Puji Astuti; Kardiyem; Rediana Setiyani; Lyna Latifah (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) AMIK Indonesia, 2023)
The local economy is currently a major issue in community development. Develop the local economy based on its potential to be developed into products of outstanding quality in the region. Purple onion is a local brainchild found in Toroh district. The abundant supply of chives is inversely proportional to the weak bargaining position due to the oversupply that occurred during the main harvest. This causes the price that farmers receive to decrease. Farmers have not been able to turn purple onions into processed products with high economic value. In fact, farmers do not have the necessary knowledge and skills to produce products processed from chives. Training on diversifying products made from chives may be a suitable solution to overcome this problem. The goal of this community service activity is to help optimize the potential of local raw materials in the form of chives to transform into products with high economic value. The method applied is a participatory method with a local economic development model that includes many stages, specifically meetings with representatives of farmer groups, Focus Group Discussions, training on production products, partner support, and monitoring and evaluation. Based on the results of the training, it was found that the local potential of onions, previously untapped, can now be optimized by farmers by producing processed products from chives. The processed products produced are fried shallots and pancakes made from dried shallots.